Соціальні смисли розвитку сучасної освіти - Утюж, Ірина Геннадіївна (My University, 2014)
Основними детермінантами змін освітніх парадигм завжди були процеси, які охоплюють весь спектр соціального, економічного й політичного життя суспільства. Ці процеси ми й розглянемо далі. The paper analyzes the social and cultural dynamics of the grounds of the current situation in education. This is the modern world - a systematic orientation of the state educational policy in the mobile coordinate system: on the one hand – mainstream coordinates of Western civilization as a metropolis that other actors are perceived as universal, on the other hand – semi - peripheral and peripheral coordinates acting on a background of modern social life as backward cultural segments.